Extraction of added-value products from biomass using ionic liquids - Silva, Ana Filipa Martins Cláudio da (2014)
The main purpose of this thesis is to investigate the potential of ionic liquids (ILs) as a new class of extractive solvents for added-value products from biomass. These include phenolic compounds (vanillin, gallic, syringic and vanillic acids), alkaloids (caffeine) and aminoacids (L-tryptophan). The interest on these natural compounds relies on the wide variety of relevant properties shown by those families and further application in the food, cosmetic and pharmaceutical industries. Aiming at developping more benign and effective extraction/purification techniques than those used, a comprehensive study was conducted using aqueous biphasic systems (ABS) composed of ILs and inorganic/organic salts. In addition, ILs were characterized by a polarity scale, using solvatochromic probes, aiming at providing prior indications on the ILs affinity for particular added-value products. Solid-liquid (S-L) extractions from biomass and using aqueous solution of ILs were also investigated. In particular, and applying and experimental factorial design to optimize the operational conditions, caffeine was extracted from guaraná seeds and spent coffee. With both types of extractions it was found that it is possible to recover the high-value compounds and to recycle the IL and salt solutions. Finally, aiming at exploring the recovery of added-value compounds from biomass using a simpler and more suistainable technique, the solubility of gallic acid, vanillin and caffeine was studied in aqueous solutions of several ILs and common salts. With the gathered results it was possible to demonstrate that ILs act as hydrotropes and that water can be used as an adequate antisolvent. This thesis describes the use of ILs towards the development of more effective and sustainable processes.